Universal salvation in late antiquity: Porphyry of Tyre and the Pagan-Christian debate - Simmons, Michael Bland (Oxford studies in late antiquity, 2015)
Porphyry of Tyre : life & historical contexts -- Contextualizing a Porphyrian soteriology -- De philosophia ex oraculis : soteriological structure and contents -- The contra Christianos in the context of universalism -- Eusebius and Porphyry : the theophany -- The historical and cultural context of universalism -- The meaning of salvation in a Greco-Roman milieu -- The Philosophia ex oraculis : a tripartite soteriological universalism -- Porphyry & Iamblichus -- Eschatological salvation -- Historical context : Caracalla to Constantine -- Religious universalism : paganism and Christianity -- Conclusions